University knowledge and firm innovation: Evidence from European countries - Andrea Bellucci; Luca Pennacchio (Institut für Angewandte Wirtschaftsforschung (IAW), 2014)
In recent decades firms have intensified the exploration of external sources of knowledge to enhance their innovation capabilities. This paper presents an empirical analysis of the factors that affect the importance of academic knowledge for firms' innovative activities. An integrated approach that simultaneously considers country-level and firm-level factors is adopted. Regarding the former factors, the analysis shows that the entrepreneurial orientation of university and the quality of academic research increase the importance of knowledge transfers from universities to firms. This suggests that the environmental and institutional context contribute to explain cross-national disparities in university-industry interactions and in the effectiveness of knowledge transfer. In regard to the latter factors, the results indicate that firms oriented toward open search strategies and radical innovations are more likely to draw knowledge from universities. Furthermore, firms belonging to high technology sectors and firms with high absorptive capacity place greater value on the various links with universities. With respect to firm size the estimates show an inverted U-shaped relation with the importance of universities as a source of knowledge. However, the greatest benefits from interacting with universities are achieved by small and young research-active firms.
Keywords: O32; O33; L20; 330; innovation; industry-university links; knowledge transfer; university entrepreneurial orientation